Matens kulturella död och återuppståndelse - Marshall, Matilda (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
Using metaphors of death, the article explores food’s different phases of edibility in terms of perceptions and habits. Perceptions of dirt and expiry dates are cultural factors which may influence the disposal as well as ideas about potentially harmful decay, such as mould. Wasted food can be resurrected by dumpster divers performing attempts of resuscitation in supermarkets’ containers. Additionally, composting and transformation into bio-fuel can turn food waste into new and useful matter. The waste is thus is in a constant flux and incorporated into the aspiration for a sustainable society.